Student's perceptions of the Jawi (Arabic Script) curriculum in Malaysia - Mamat , Arifin; Abd Rashid, Adnan; Khamis, Rohani (The Islamic Cultural Centre and London Central Mosque, London, 2013)
Islamic Education is one of the core subjects offered in Malaysian primary schools, but studies reveal a weakness in Jawi (Arabic script) skills. The Ministry of Education has therefore designed a special programme called jQAF to enhance students' abilities in Jawi, the Qur'an, Arabic and Fard'Ain. This study attempts to investigate the strategies applied by Islamic Education teachers in Jawi. The researcher has conducted a case study using questionnaires. The respondents comprised 112 male and 143 female year six students from selected government primary schools in the district of Hulu Selangor. A descriptive analysis has been employed to provide meanings to the data. The simple descriptive statistical analysis includes percentage, frequencies and means. It was revealed that four methods had been used; flash cards, drill technique, playing games and learning through songs. The findings also revealed that there are several methods applied by teachers of Jawi. It was also found that students have positive perceptions about Jawi. Generally, this study provides useful insights that can benefit those involved in the field of Islamic Education.